Les partis politiques égyptiens dans la révolution - Clément Steuer (L’Année du Maghreb)
This article suggests a classification of political parties in Mubarak’s Egypt, based on their level of integration into the former regime, according to the combinatorial analysis of two elements : on the one hand, the resources provided directly or indirectly by the executive, on the other hand, the various resources independent from the State, and unevenly distributed among the party organizations. Provided that a party devoid of all resources is obviously doomed to disappear, the combination of the two variables used here helps us classify the Egyptian parties into three categories : parties excluded from the system, parties co-opted and incorporated into the system and finally artificial parties, who have practically no resources of their own and are therefore extremely dependent on the central power. During the revolution, the latter had no choice but to defend the regime, if not actively, at least by their wait-and-see attitude. Co-opted parties however have a genuine existence in society, independent from State support, but they have been given a number of advantages by the State. Consequently, they did not attempt to challenge the regime and remained on the sidelines of the protest movements that proliferated over the past decade. Finally, the parties excluded from the system owe nothing to the political nucleus and were thus the most interested in a change in regime. Therefore they took an active part in the above mentioned protest activities. This typology offers an interpretative framework explaining the different positions taken by the parties during the Egyptian revolution, taking into account not only their immediate interests, but also the range of actions available to them and their proximity to the protest movements, given that the latter two elements are inherited from past behaviors.